2010
DOI: 10.1016/j.jmb.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Par-4 Recognition by the SPRY Domain- and SOCS Box-Containing Proteins SPSB1, SPSB2, and SPSB4

Abstract: The mammalian SPRY domain- and SOCS box-containing proteins, SPSB1 to SPSB4, belong to the SOCS box family of E3 ubiquitin ligases. Substrate recognition sites for the SPRY domain are identified only for human Par-4 (ELNNNL) and for the Drosophila orthologue GUSTAVUS binding to the DEAD-box RNA helicase VASA (DINNNN). To further investigate this consensus motif, we determined the crystal structures of SPSB1, SPSB2, and SPSB4, as well as their binding modes and affinities for both Par-4 and VASA. Mutation of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 34 publications
4
86
0
Order By: Relevance
“…2A). This structurally divergent protein face forms the binding interface in TRIM21,Gustavus, and SPSB1-4 proteins, the interactions of which with their binding partners have been structurally characterized (24,26,27). In primate TRIM5α, the residues that display strong positive selection in recent evolution as well as sequence insertion sites map to the same protein surface (10,11,13), offering strong evidence that the TRIM5α PRYSPRY uses the same interface for binding to the retroviral capsids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A). This structurally divergent protein face forms the binding interface in TRIM21,Gustavus, and SPSB1-4 proteins, the interactions of which with their binding partners have been structurally characterized (24,26,27). In primate TRIM5α, the residues that display strong positive selection in recent evolution as well as sequence insertion sites map to the same protein surface (10,11,13), offering strong evidence that the TRIM5α PRYSPRY uses the same interface for binding to the retroviral capsids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…U87MG (H) cells were transfected with 20 nM control or SPSB1 siRNA and pCAGA 12 -luc for 24 h and subsequently infected with adenovirus carrying TGF-␤-driven tdTomato expression (pAd-CAGA-tdTomato) for another 24 h. Cells were then treated with or without TGF-␤ (2 ng/ml) for a further 24 h. Live cell images were taken using a fluorescent microscope (magnification, ϫ20). ent in multiple target proteins (37,57,58), it is possible that this represents a direct interaction between SPSB1 and T␤RII. Alternatively, another (as yet unknown) protein may act as an adaptor to bring SPSB1 to the T␤RII complex.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SPSB1 and -2 recognize a similar sequence motif in Par4 and iNos: Glu/Asp-Leu/Ile-AsnAsn-Asn-Leu ((E/D)(L/I)NNN)). In particular, the Asn-AsnAsn sequence was crucial for their interaction (37,57,58). Our sequence alignment shows that T␤RII shares no overall sequence similarity with Par4 but contains a stretch of Asn 234 -Ile-Asn-His-Asn-Thr 239 (NINHNT) at the N terminus of the intracellular domain of the receptor.…”
Section: Tgf-␤ Induces Spsb1 Transcription Which Acts In a Feedback mentioning
confidence: 99%
“…and Asn27) [2]. Further binding studies by surface plasmon resonance (SPR) experiments revealed the linear DINNN peptide bound to SPSB2 with a K D of 318 nM [3], suggesting that the flanking residues of the DINNN sequence in the N-terminal region of iNOS contributed to its low nanomolar binding affinity to SPSB2.…”
mentioning
confidence: 99%